149k views
0 votes
Can anyone please help

Can anyone please help-example-1
User Kevin Cox
by
4.6k points

2 Answers

5 votes

Answer:

1)
f'(x)=-(24x)/((5+x^2)^2)

2)
f'(2)=-(16)/(27)

Explanation:

So we have the function:


f(x)=(7-x^2)/(5+x^2)

And we want to find f'(x).

To do so, we can use the quotient rule.

So, let's take the derivative of both sides:


(d)/(dx)[f(x)]=(d)/(dx)[(7-x^2)/(5+x^2)]

Remember that the quotient rule is:


(d)/(dx)[f/g]=(f'g-fg')/(g^2)

In our equation, f is (7-x^2) and g is (5+x^2).

So, using the quotient rule, our derivative f'(x) is:


f'(x)=((d)/(dx)[7-x^2](5+x^2)-(7-x^2)(d)/(dx)[5+x^2])/((5+x^2)^2)

Differentiate:


f'(x)=((-2x)(5+x^2)-(7-x^2)(2x))/((5+x^2)^2)

Simplify. Distribute in the numerator:


f'(x)=((-10x-2x^3)-(14x-2x^3))/((5+x^2)^2)

Distribute:


f'(x)=((-10x-2x^3)+(-14x+2x^3))/((5+x^2)^2)

The cubed terms cancel. This leaves:


f'(x)=((-10x)+(-14x))/((5+x^2)^2)

Add. So, our derivative is:


f'(x)=-(24x)/((5+x^2)^2)

To find f'(2), simply substitute 2 into our derivative. So:


f'(2)=-(24(2))/((5+(2)^2)^2)

Multiply and square:


f'(2)=-(48)/((5+4)^2)

Add:


f'(2)=-(48)/((9)^2)

Square:


f'(2)=-(48)/(81)

Reduce by 3:


f'(2)=-(16)/(27)

And we're done!

User Greg Van Gorp
by
4.6k points
7 votes


\text{Hi there! :)}


\large\boxed{f'(2) = -(16)/(27) }


f'(x) = ((5 + x^(2) )(-2x) - (7 - x^(2) )(2x))/((5+x^(2))^(2) ) \\\\f'(x) = (-10x-2x^(3)- 14x + 2x^(3) )/((5+x^(2))^(2) ) \\\\f'(x) = (-24x)/((5+x^(2))^(2) )\\\\ \text{Solve for the derivative at f'(2) using substitution:}\\\\f'(2) = (-24(2))/((5+2^(2))^(2) ) \\\\f'(2) = (-48)/(81) \\\\\text{Simplify:}\\\\f'(2) = -(16)/(27)

User Andrey Mishchenko
by
5.2k points